2022
DOI: 10.1002/essoar.10510317.1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Challenges in hydrologic-land surface modelling of permafrost signatures - Impacts of parameterization on model fidelity under the uncertainty of forcing

Abstract: Permafrost plays an important role in the hydrology of arctic/subarctic regions. However, permafrost thaw/degradation has been observed over recent decades in the Northern Hemisphere and is projected to accelerate. Hence, understanding the evolution of permafrost areas is urgently needed. Land surface models (LSMs) are well-suited for predicting permafrost dynamics due to their physical basis and large-scale applicability. However, LSM application is challenging because of the large number of model parameters … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 81 publications
(136 reference statements)
0
2
0
Order By: Relevance
“… The gradual reduction in ZSNL value, the most sensitive permafrost parameter in the MESH model (Abdelhamed et al, 2022b), resulted in a drastic reduction in PE (and PA of ~77,000 km 2 ) in Exp. 4 vs. Exp.…”
Section: Gridded Datasetsmentioning
confidence: 99%
See 1 more Smart Citation
“… The gradual reduction in ZSNL value, the most sensitive permafrost parameter in the MESH model (Abdelhamed et al, 2022b), resulted in a drastic reduction in PE (and PA of ~77,000 km 2 ) in Exp. 4 vs. Exp.…”
Section: Gridded Datasetsmentioning
confidence: 99%
“…3. Based on a previous global sensitivity analysis (Abdelhamed et al, 2022b), permafrost 325 simulation was found to be highly sensitive to two sets of parameters, representing surface insulation by snow cover (represented by the minimum snow depth to consider 100% ground snow cover, ZSNL) and soil texture, especially related to organic matter (type, vertical distribution, and depth of organic soil 'ODEP'), which collectively contribute ≥50% of the total sensitivity of permafrost simulation. The remaining parameters are either entirely insensitive (eight parameters with <1% contribution) or have low-to-moderate sensitivity (15 parameters with 1-10% contribution).…”
mentioning
confidence: 99%